2002
DOI: 10.7863/jum.2002.21.11.1249
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Bladder Disorders in Female Lower Urinary Tract Symptoms on Ultrasonographic Cystourethrography

Abstract: Objective. To evaluate morphologic features of bladder disorders in female lower urinary tract symptoms using ultrasonographic cystourethrography and to elucidate the anatomic association of these morphologic characteristics. Methods. Ultrasonographic cystourethrography was performed in 1049 women with lower urinary tract symptoms and 1 single urodynamic diagnosis, including 764 patients with genuine stress incontinence, 190 with detrusor instability, and 95 with a hypersensitive bladder. Thirty-six women with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 12 publications
4
36
0
1
Order By: Relevance
“…In an update of the systematic review on the diagnostic accuracy of BWT in diagnosing DO (unpublished data: Suneetha Rachaneni, University of Birmingham, 2015) 21 studies 28,[49][50][51][52][53][54][55][56][57][58][59]72,97,[113][114][115][116][117][118][119] have been identified that have investigated the relationship between BWT measured by ultrasonography and DO, results from which for the sensitivity, specificity and AUC for bladder ultrasonography vary from 37% to 91%, 61% to 97% and 0.61-0.91, respectively (see Appendix 7). The studies draw mixed conclusions, ranging from…”
Section: Placing the Results In The Context Of Other Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In an update of the systematic review on the diagnostic accuracy of BWT in diagnosing DO (unpublished data: Suneetha Rachaneni, University of Birmingham, 2015) 21 studies 28,[49][50][51][52][53][54][55][56][57][58][59]72,97,[113][114][115][116][117][118][119] have been identified that have investigated the relationship between BWT measured by ultrasonography and DO, results from which for the sensitivity, specificity and AUC for bladder ultrasonography vary from 37% to 91%, 61% to 97% and 0.61-0.91, respectively (see Appendix 7). The studies draw mixed conclusions, ranging from…”
Section: Placing the Results In The Context Of Other Researchmentioning
confidence: 99%
“…54 A subsequent update to the review identified seven further studies that have shown a significantly increased BWT in patients with DO than in patients without DO. 27,50,[55][56][57][58][59] However, the heterogeneity in the methods, including the standardisation of bladder ultrasonography and of UDS, and poor reporting of the proportions of DO cases identified as well as missed, precludes a formal diagnostic meta-analysis. Other methodological weaknesses of prior studies include unclear description of how bladder ultrasonography and UDS results were blinded to each other, recruitment mainly from a single centre and retrospective design.…”
Section: Bladder Ultrasonographymentioning
confidence: 99%
See 1 more Smart Citation
“…From January 2002 to January 2003, 138 consecutive women with lower urinary tract symptoms (frequency, nocturia, urgency, urge or stress incontinence, or voiding dysfunction) for at least 3 months who had undergone functional evaluation of the lower urinary tract by multichannel urodynamic testing together with morphological assessment of the lower urinary tract by ultrasound cystourethrography7, 9 were enrolled in this study. Exclusion criteria included: (1) hematuria, recurrent dysuria, abnormal urinalysis or positive urine culture; (2) a history of pelvic surgery, neuropathy (central or peripheral), diabetes mellitus or radiation therapy or (3) estrogen replacement therapy for postmenopausal symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…We performed introital and transvaginal ultrasonography with a Toshiba SSA‐260A (Toshiba, Tokyo, Japan) or Voluson 730 (Medison‐Kretztechnik, Zipf, Austria) scanner and an endovaginal probe with a frequency range of 5.0–9.0 MHz. The morphology of the lower urinary tract was evaluated at rest and during a maximum Valsalva maneuver as described in a previous study9. Color Doppler imaging was performed with pulse repetition frequency of 4.0 kHz and wall filters of 50 Hz.…”
Section: Methodsmentioning
confidence: 99%